The behavioural and cognitive impacts of digital educational interventions in the emergency department: A systematic review. - Sophie Cleff; Shubhang Sreeranga; Ibtisam Mahmoud; Abdullatif Hassan; Laury Gueyie Noutiamo; Elie Fadel; Jennifer Turnbull; Esli Osmanlliu (PLOS Digital Health)
Ensuring patients and their caregivers understand the health information they receive is an important part of every clinical visit. Digital educational interventions like video discharge instructions, follow-up text messaging, or interactive web-based modules (WBMs) have the potential to improve information retention and influence behaviour. This study aims to systematically evaluate the impact of these interventions on patient and caregiver cognition and behaviour, as well as identify the characteristics of successful interventions and observe how success is measured. In December of 2022, a systematic literature search was conducted in several databases (Cochrane, Embase, MEDLINE (Ovid), Web of Science, ClinicalTrials.gov, and Google Scholar) for randomized controlled trials (RCTs) published between 2012 and 2022. In 2024, an identical search was performed for articled published between 2022 and 2024. Studies testing patient- and caregiver-facing digital educational interventions in the emergency department for behavioural and cognitive outcomes were included. Data from 35 eligible studies encompassing 12,410 participants were analyzed and assessed for bias using the Cochrane RoB2.0 tool. Video was used in 22 studies (63%), making it the most common modality. Seventy-three percent (16/22) of these studies reported statistically significant improvements in their primary outcomes. Text messaging was used in eight studies, with two (25%) reporting significant improvement in their primary outcomes. WBMs and apps were used in seven studies, 71% (5/7) of which reported statistically significant improvements in primary outcomes. Statistically significant improvements in cognitive outcomes were reported in 64% (18/28) of applicable studies, compared with 17% (4/23) for behavioural outcomes. The results suggest that digital educational interventions can positively impact cognitive outcomes in the emergency department. Video, WBM, and app modalities appear particularly effective. However, digital educational interventions may not yet effectively change behaviour. Establishing guidelines for evaluating the quality of digital educational interventions, and the formal adoption of existing reporting guidelines, could improve study quality and consistency in this emerging field. Registration The study is registered with PROSPERO ID #CRD42023338771.